PREPARATION OF MONOSPECIFIC BRUCELLA ANTI-ABORTUS SERUM BASED ON THERMOEXTRACT FROM S-FORM BRUCELLA - L. M. Мikhailov; N. L. Barannikova; L. E. Tokareva; N. M. Andreevskaya; V. A. Мikhailova; V. I. Kuznetsov; K. Yu. Yastremskaya; S. V. Balakhonov (Проблемы особо опасных инфекций, 2017)
Objective of the study is to prepare rabbit monospecific anti-abortus serum to a Brucella S-form thermoextract, as well as to evaluate its activity and specificity. Materials and methods. Utilized was polyvalent hyperimmune serum obtained to Brucella thermoextract. It was adsorbed by a strain of heterologous species Brucella melitensis 16 N. Reference, vaccinal and field Brucella strains were used to estimate the activity and specificity of the serum produced. Results and conclusions. This serum possesses high activity (1:160, 1:320 titer) and specificity, and the results completely coincide with the data specified in the table of differential properties presented in МR 3.1.7.1189-03 “Prophylaxis and laboratory diagnostics of human brucellosis». The outlined method for manufacturing monospecific Brucella anti-abortus serum permits for a considerable decrease in biological hazard for personnel involved in the technological operations.